(untitled) (Research, Society and Development, 2022)
The use of medicinal plants by man, a process known as phytotherapy, has always been present in human history. Activities related to home medicine offered by traditional midwives are works of regional cultures in which the needs of the population prioritize alternative health practices. From this perspective, the objective of this study was to conduct an ethnobotanical survey on the use of medicinal plants, as well as their purposes, by midwives in the municipality of Serra Talhada - PE. We interviewed 11 women called midwives in rural and urban areas, aged between 56 and 70 years, in order to promote a survey on the use of medicinal plants used by them. Fourteen plant species with medicinal applications during childbirth processes were reported, with the highest number of citations for Myracrodruon urundeuva Allemão (aroeira) and Ximenia americana L (ameixa do mato). The most frequent uses are related to anti-inflammatory and healing processes. The species are distributed in 10 families, with greater representation for Fabaceae and Anacardeaceae. The results obtained are similar to the literature consulted, in a way that praises the traditional knowledge, subjugated by science.